A Marginal Note to “Four Sistine Ethiopians?” - Fiaccadori, Gianfranco (Aethiopica, 2011)
With reference to Marco Bonechi’s article in this issue of Aethiopica, the present paper briefly surveys the evidence for the 1481 Ethiopian “embassy” to Pope Sixtus IV and then explores the possibility of identifying Anthony, head of that embassy, with “Fra Antonio Abissino” portrayed, most likely before 1527 by a painter called Schizzone, on the now lost tramezzo (‘choir screen’) of the Vatican church of Santo Stefano dei Mori.